Calorimetric measurements of the Ca-Li liquid alloys - Debski, Adam; Garzeł, Grzegorz; Zakulski, Wojciech; Gąsior, Władysław (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
An isothermal high-temperature mixing calorimeter was used for the determination of the enthalpy of mixing ΔmixH for liquid Ca-Li solutions, for 63 alloys of different compositions at the four following temperatures: 588 K, 648 K, 820 K and 1159 K. The studies were performed by way of dropping solid metal samples at ambient temperature into liquid alloys, starting from pure elements. In three series, calcium was dropped into liquid lithium, whereas solid Li samples were added into liquid Ca in the fourth series. Because of the high reactivity of the alloy components, all the steps of the experiment were conducted in a high purity argon atmosphere. It was found that the Ca-Li system is characterized by small negative ΔmixH values and its minimal value is lower than -1.5 kJ/mol. Additionally, the differential thermal analysis was used to determine the phase transformation temperature for 11 Ca-Li alloys.Finally, the Calphad method was used to assess the phase diagram, applying the data of these studies as well as all the experimental results available in the literature.